Studi Kinetika Adsorpsi Ion Au(III) Menggunakan Kulit Buah Manggis (Garcinia mangostana L.) - Mellia Harumi; Faisal Shaleh; Sri Sudiono; Triyono Triyono (Soegijapranata Catholic University, 2020)
Adsorption using biosorbent become an alternatif for recovery heavy metals such as gold from electronic waste. Mangosteen rind can adsorp Au(III) ions in acid condition pH 2 optimally. Kinetics study of Au(III) ions adsorption using mangosteen rind was aim to determine adsorption kinetics model, adsorption rate constanta (k) and activation energy (Ea) Au(III) ions using mangosteen rind. Adsorbent. Adsorbent preparation was carried out using maceration methof for activate adsorption functional group and remove contaminant materials. Au(III) ions adsorption was analyzed by varying temperature and time. Adsorbed Au(III) was determined using Atomic Adsorption Spectroscopy (AAS) and characterized using Fourier Transform Infra Red (FTIR) Spectroscopy dan X-Ray Diffraction (XRD) Spectroscopy. The result proved that KBM adsorbent could adsorp Au(III) ions effectivelly and follow Ho pseudo-second order kinetic with Ea of 24,65 kJ/mol and k of 2.05x10-3 ( 40℃); 3.63x10-3 ( 50℃) dan 3.60x10-3 ( 60℃) g mg-1 minutet-1 respectivelly.